Consensus of the Brazilian Headache Society (SBCe) for the Prophylactic Treatment of Episodic Migraine: part I - Eliana Meire Melhado; Paulo Sergio Faro Santos; Alexandre Ottoni Kaup; Aline Turbino Neves Martins da Costa; Célia Aparecida de Paula Roesler; Élcio Juliato Piovesan; Elder Machado Sarmento; Giselle Oliveira Martins Theotonio; Henrique Carneiro de Campos; Ida Fortini; Jano Alves de Souza; Jayme Antunes Maciel Júnior; et al. (Arquivos de Neuro-Psiquiatria)
The Brazilian Headache Society (Sociedade Brasileira de Cefaleia, SBCe, in Portuguese) nominated a Committee of Authors with the aim of establishing a consensus with recommendations regarding prophylactic treatment for episodic migraine based on articles published in the worldwide literature, as well as personal experience. Migraine affects 1 billion people around the world and more than 30 million Brazilians. In addition, it is an underdiagnosed and undertreated disorder. It is well known within the medical community of neurologists, and especially among headache specialists, that there is a need to disseminate knowledge about prophylactic treatment for migraine. For this purpose, together with the need for drug updates and to expand knowledge of the disease itself (frequency, intensity, duration, impact and perhaps the progression of migraine), this Consensus was developed, following a full online methodology, by 12 groups who reviewed and wrote about the pharmacological categories of the drugs used and, at the end of the process, met to read and establish conclusions for this document. The drug classes studied were: anticonvulsants, tricyclic antidepressants, monoclonal anti-calcitonin gene-related peptide (anti-CGRP) antibodies, beta-blockers, antihypertensives, calcium channel inhibitors, other antidepressants (selective serotonin reuptake inhibitors, SSRIs, and dual-action antidepressants), other drugs, and polytherapy. Hormonal treatment and anti-inflammatories and triptans in minimum prophylaxis schemes (miniprophylaxis) will be covered in a specific chapter. The drug classes studied for part I of the Consensus were: anticonvulsants, tricyclic antidepressants, monoclonal anti-CGRP antibodies, and beta-blockers.